The Effect of Acoustic Music Therapy in Overcoming Anxiety in Generation Z in Purwakarta Regency, Indonesia - Lailatun, Lailatun (Arkus, 2024)
Anxiety is one of the most common mental health problems experienced by generation Z. Acoustic music therapy is an alternative therapy that can be used to treat anxiety. This study aims to examine the effect of acoustic music therapy in overcoming anxiety in generation Z in Purwakarta Regency, Indonesia. This research uses a quasi-experimental research design with a pretest-posttest control group design. The research sample consisted of 60 people, who were divided into two groups, namely the acoustic music therapy group (30 people) and the control group (30 people). The acoustic music therapy group was given acoustic music therapy for 8 weeks, while the control group was not given any therapy. The results showed that there was a significant difference between the acoustic music therapy group and the control group in terms of anxiety levels. The acoustic music therapy group experienced a greater reduction in anxiety levels than the control group. Based on the results of this research, it can be concluded that acoustic music therapy is effective in overcoming anxiety in generation Z.